MORAL VALUES AND CULTURAL IDENTITY IN INDONESIANCHILDREN’S SONG LYRICS: A DISCOURSE ANALYSIS: A Discourse Analysis - Eka Nur Ramadhani; Gisca Tri Maura Kunti; Sofi Sofi Nurazizah; Suci Chalista; Yovanka Digna Margareta; Siamir Marulafau; Erikson Saragih (Teaching English and Language Learning English Journal, 2025)
This writing entitled "Moral Values and Cultural Identity in Indonesian Children's Song Lyrics: A Discourse Analysis". This study used a qualitative discourse analysis method to find cultural identity markers, moral themes, and character education values in the language, synbols, and social environment of the song lyrics. Children's song lyrics made up the primary data, and pertinent scholarly sources on character education, cultural linguistics, and Indonesian children's song studies provided secondary data. The findings demonstrate that fundamental moral principles including obedience, discipline, cooperation, thankfulness, civility, and simplicity are reflected in the lyrics of Indonesian children's songs. Children's conceptions of the Indonesian environment are also shaped by references to nature, traditional transportation, social life, and local language patterns, all of which are manifestations of Indonesian cultural identity. It has been demonstrated that children's songs are essential for moral, social, and cultural education. In order to guarantee that moral and cultural lessons are assimilated contextually. This study suggests reviving children's songs in the character education curriculum and including kids in song interpretation.